Frailty Phenotypes, Disability, and Outcomes in Adult Candidates for Lung Transplantation - Singer, Jonathan P.; Diamond, Joshua M.; Gries, Cynthia J.; McDonnough, Jamiela; Blanc, Paul D.; Shah, Rupal; Dean, Monica Y.; Hersh, Beverly; Wolters, Paul J.; Tokman, Sofya; Arcasoy, Selim M.; Ramphal, Kristy; et al. (American journal of respiratory and critical care medicine, 2015)
Frailty is associated with morbidity and mortality in abdominal organ transplantation but has not been examined in lung transplantation. To examine the construct and predictive validity of frailty phenotypes in lung transplant candidates. In a multicenter prospective cohort, we measured frailty with the Fried Frailty Phenotype (FFP) and Short Physical Performance Battery (SPPB). We evaluated construct validity through comparisons with conceptually related factors. In a nested case-control study of frail and nonfrail subjects, we measured serum IL-6, tumor necrosis factor receptor 1, insulin-like growth factor I, and leptin. We estimated the association between frailty and disability using the Lung Transplant Valued Life Activities disability scale. We estimated the association between frailty and risk of delisting or death before transplant using multivariate logistic and Cox models, respectively. Of 395 subjects, 354 completed FFP assessments and 262 completed SPPB assessments; 28% were frail by FFP (95% confidence interval [CI], 24-33%) and 10% based on the SPPB (95% CI, 7-14%). By either measure, frailty correlated more strongly with exercise capacity and grip strength than with lung function. Frail subjects tended to have higher plasma IL-6 and tumor necrosis factor receptor 1 and lower insulin-like growth factor I and leptin. Frailty by either measure was associated with greater disability. After adjusting for age, sex, diagnosis, and transplant center, both FFP and SPPB were associated with increased risk of delisting or death before lung transplant. For every 1-point worsening in score, hazard ratios were 1.30 (95% CI, 1.01-1.67) for FFP and 1.53 (95% CI, 1.19-1.59) for SPPB. Frailty is prevalent among lung transplant candidates and is independently associated with greater disability and an increased risk of delisting or death.